Twin/Multiple Gestations With a Hydatidiform Mole: Clinicopathologic Analysis of 21 Cases With Emphasis on Molecular Genotyping and Parental Contribution. (6th September 2022) - Xing, Deyin; Adams, Emily; Zou, Ying S.; Morsberger, Laura; Scanga, Lori R.; Gao, Faye F.; Barker, Norman; Vang, Russell; Ronnett, Brigitte M.
Abstract : Complete hydatidiform moles (CHMs) and partial hydatidiform moles (PHMs) are abnormal gestations characterized by vesicular chorionic villi accompanied by variable trophoblastic hyperplasia, with or without embryonic development. CHMs are purely androgenetic (only paternal [P] chromosome complements), mostly homozygous/monospermic ( 85%) but occasionally heterozygous/dispermic, whereas PHMs are overwhelmingly diandric triploid (2 paternal [P] and 1 maternal [M] chromosome complements) and heterozygous/dispermic (>95%). The presence of a fetus in a molar pregnancy usually indicates a PHM rather than a CHM; however, CHMs and PHMs rarely can be associated with a viable fetus or a nonmolar abortus in twin pregnancies and rare multiple gestation molar pregnancies have been reported. A "one-oocyte-model, " with diploidization of dispermic triploid zygotes, has been proposed for twin CHM with coexisting fetus, and a "two-oocyte-model" has been proposed for twin PHM with coexisting fetus. Among 2447 products of conception specimens, we identified 21 cases of twin/multiple gestations with a molar component, including 20 CHMs (17 twins, 2 triplets, 1 quintuplet) and 1 PHM (twin). P57 immunohistochemistry was performed on all; DNA genotyping of molar and nonmolar components was performed on 9 twin CHMs, 1 triplet CHM, 1 quintuplet CHM, and 1 twin PHM. All CHM components were p57-negative and those genotyped were purely androgenetic. Twin CHMs had genotypes of P1M1+P2P2 in 5, P1M1+P1P1 in 1, and P1M1+P2P3 in 1, consistent with involvement of 1 oocyte and from 1 to 3 sperm—most commonly a homozygous CHM but involving 2 sperm in the whole conception—and compatible with a "one-oocyte-model." The triplet CHM was P1M1+P1P1+P2M2 and the quintuplet CHM was P1M1+P2M2+P2M2+P3M3+P4P4, consistent with involvement of 2 sperm and at least 2 oocytes for the triplet and 4 sperm and at least 3 oocytes for the quintuplet. The twin PHM had a P1M1+P2P3M2 genotype, consistent with involvement of 2 oocytes and 3 sperm. p57 immunohistochemistry is highly reliable for diagnosis of CHMs in twin/multiple gestations. Refined diagnosis of molar twin/multiple gestations is best accomplished by correlating morphology, p57 immunohistochemistry, and molecular genotyping, with the latter clarifying zygosity/parental chromosome complement contributions to these conceptions.